Ethnic Minority Immigrants and their Children in Britain - Christian Dustmann; Nikolaos Theodoropoulos (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2006)
According to the 2001 UK Census ethnic minority groups account for 4.6 million or 7.9 percent of the total UK population. The 2001 British Labour Force Survey indicates that the descendants of Britain's ethnic minority immigrants form an important part of the British population (2.8 percent) and of the labour force (2.1 percent). In this paper, we use data from the British Labour Force Survey over the period 1979-2005 to investigate educational attainment and economic behaviour of ethnic minority immigrants and their children in Britain. We compare different ethnic minority groups born in Britain to their parent's generation and to equivalent groups of white native born individuals. Intergenerational comparisons suggest that British born ethnic minorities are on average more educated than their parents as well more educated than their white native born peers. Despite their strong educational achievements, we find that ethnic minority immigrants and their British born children exhibit lower employment probabilities than their white native born peers. However, significant differences exist across immigrant/ethnic groups and genders. British born ethnic minorities appear to have slightly higher wages than their white native born peers. But if British born ethnic minorities were to face the white native regional distribution and were attributed white native characteristics, their wages would be considerably lower. The substantial employment gap between British born ethnic minorities and white natives cannot be explained by observable differences. We suggest some possible explanations for these gaps.
Keywords: J15; I20; J62; J21; J30; 330; Ethnic Minorities/Immigrants; Education; Intergenerational comparisons; Employment; Wages